Global health systems partnerships: a mixed methods analysis of Mozambique's HPV vaccine delivery network actors - Caroline Soi; Jessica Shearer; Baltazar Chilundo; Vasco Muchanga; Luisa Matsinhe; Sarah Gimbel; Kenneth Sherr (BMC, 2020)
Abstract Background Global health partnerships have expanded exponentially in the last two decades with Gavi, the Vaccine Alliance considered the model's pioneer and leader because of its vaccination programs' implementation mechanism. Gavi, relies on diverse domestic and international partners to carry out the programs in low- and middle-income countries under a partnership engagement framework (PEF). In this study, we utilized mixed methods to examine Mozambique's Gavi driven partnership network which delivered human papillomavirus (HPV) vaccine during the demonstration phase. Methods Qualitative tools gauged contextual factors, prerequisites, partner performance and practices while a social network analysis (SNA) survey measured the partnership structure and perceived added value in terms of effectiveness, efficiency and country ownership. Forty key informants who were interviewed included frontline Ministry of Health workers, Ministry of Education staff and supporting partner organization members, of whom 34 participated in the social network analysis survey. Results Partnership structure SNA connectivity measurement scores of reachability (100%) and average distance (2.5), were high, revealing a network of very well-connected HPV vaccination implementation collaborators. Such high scores reflect a network structure favorable for rapid and widespread diffusion of information, features necessary for engaging and handling multiple implementation scales. High SNA effectiveness and efficiency measures for structural holes (85%) and low redundancy (30%) coupled with high mean perceived effectiveness (97.6%) and efficiency (79.5%) network outcome scores were observed. Additionally, the tie strength average score of 4.1 on a scale of 5 denoted high professional trust. These are all markers of a collaborative partnership environment in which disparate institutions and organizations leveraged each entity's comparative advantage. Lower perceived outcome scores for country ownership (24%) were found, with participants citing the prominent role of several out-of-country partner organizations as a major obstacle. Conclusions While there is room for improvement on the country ownership aspects of the partnership, the expanded, diverse and inclusive collaboration of institutions and organizations that implemented the Mozambique HPV vaccine demonstration project was effective and efficient. We recommend that the country adapt a similar model during national scale up of HPV vaccination.